Milk consumption and the risk of type 2 diabetes: A systematic review of Mendelian randomization studies - Jensen, Christopher Fisker; Timofeeva, Maria; Berg-Beckhoff, Gabriele (Nutrition, metabolism, and cardiovascular diseases, 2023)
Previously, no relationship between milk consumption and the risk of type 2 diabetes has been found in prospective cohorts. However, Mendelian randomization allows researchers to almost bypass much residual confounding, providing a more precise effect estimate. This systematic review aims to investigate the risk of type 2 diabetes and levels of HbA1c by assessing all Mendelian Randomization studies investigating this subject matter. PubMed and EMBASE were searched from October 2021 through February 2023. Inclusion and exclusion criteria were formulated to filter out irrelevant studies. Studies were qualitatively assessed with STROBE-MR together with a list of five MR criteria. Six studies were identified, containing several thousand participants. All studies used the SNP rs4988235 as the main exposure and type 2 diabetes and/or HbA1c as the main outcome. Five studies were graded as “good” with STROBE-MR, with one graded as “fair”. For the six MR criteria, five studies were graded “good” in four criteria, while two studies were graded “good” in two criteria. Overall, genetically predicted milk consumption did not seem to be associated with an increased risk of type 2 diabetes. This systematic review found that genetically predicted milk consumption did not seem to increase the risk of type 2 diabetes. Future Mendelian randomization studies concerning this topic should consider conducting two-sample Mendelian Randomization studies, in order to derive a more valid effect estimate. •In this review, genetically determined milk intake did not increase type-2 diabetes risk.•Genetically determined milk intake did not affect the level of glycated hemoglobin.•Mendelian Randomization/genetic disposition confers a low risk of confounding.